PENGARUH PEMBERIAN EKSTRAK DAUN CARICA PUBESCENS Lenne & K. koch TERHADAP KETEBALAN EPITEL GINGIVA MENCIT BETINA YANG DIPAPAR ASAP ROKOK - Aprinda Kristanti, Risma (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2017)
The exposure from cigarette smoke in long term can destroy oral mucous, thickening of the epithel gingival tissue, and keratotic white spot that sign leukoplakia and oral cancer. Several components in the C.pubescens leaf for example atsiri oil, polifenol, and flavonoid are kown has antioxidant acivity. The major component in C.pubescens leaf that have antioxidant activity is vitamin C. The aim of this study is to examine the effect of C. pubescens leaf extract to the thickness of gingival tissue from female mices that got cigarette smoke exposure. Twenty five adult female mices were devided into five group and they exposed by cigarette smoke for twenty one day. K1 group as negative control were given by cmc, K2 group as positive control were given by 0,2 mg vitamin C, K3 group were given by 0,5 g/KgBW C. pubescens extract, K4 group were given by 1 g/KgBW C. pubescens extract, and K5 group were given by 2 g/KgBW C. pubescens extract. At the end of 22nd day, the mices were sacrificed and the gingival mucosa were collected for histologist preparations.The result of this study shows that K2 group has the thickest gingival epithel layers while there is significant different among five group for the thikness gingival epithel layers.